1994
DOI: 10.1210/endo.134.1.8275967
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the rat anterior and neurointermediate pituitary visualized by immunocytochemistry for the growth-associated protein GAP-43.

Abstract: Immunocytochemical localization of the neuronal growth associated protein GAP-43 revealed a dense axonal plexus throughout the neurointermediate lobe of the rat pituitary. These axons were fine, presumably monoaminergic fibers, whereas magnocellular neurosecretory axons did not appear to contain detectable GAP-43. These experiments also revealed the presence of an extensive nerve plexus within the anterior lobe. Fine beaded fibers were present throughout the parenchyma of the anterior lobe, and punctate staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some of the authors speculated that the nerve fibers are autonomic in nature (Rosenfeld et al 1983;Mikkelsen et al 1989). Recently, tyrosine hydroxylase-and GAP-43-like immunoreactive (LI) nerve fibers were also found to be present (Paden et al 1994;Bayet et al 1994). Our recent studies have demonstrated substantial amounts of peptidergic nerve fibers in the anterior pituitary of several mammalian species.…”
Section: Introductionmentioning
confidence: 86%
“…Some of the authors speculated that the nerve fibers are autonomic in nature (Rosenfeld et al 1983;Mikkelsen et al 1989). Recently, tyrosine hydroxylase-and GAP-43-like immunoreactive (LI) nerve fibers were also found to be present (Paden et al 1994;Bayet et al 1994). Our recent studies have demonstrated substantial amounts of peptidergic nerve fibers in the anterior pituitary of several mammalian species.…”
Section: Introductionmentioning
confidence: 86%
“…Omission of the primary antibody served as the immunohistochemi¬ cal method control. For specificity of the antibody and details of the preabsorption test, see Paden et al (1994). Preabsorption of the antibody with GAP-43 purified from neonatal rat cerebral cortex completely eliminated immunoreactivity in the pituitary.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The present data indicate that bGH can be neurally regulated. Additional data supporting the idea of neural as well as humoral regulation of the anterior pituitary have been published (20,22,23). Afferent pathways have been demonstrated that project from rat hindlimb muscles to hypothalamic nuclei, including the paraventricular nucleus, which has a known role in iGH regulation (5,7).…”
mentioning
confidence: 92%
“…Afferent pathways have been demonstrated that project from rat hindlimb muscles to hypothalamic nuclei, including the paraventricular nucleus, which has a known role in iGH regulation (5,7). Furthermore, nerve fibers have been observed surrounding hormone-producing cells (somatotrophs, corticotrophs) in the anterior pituitary of the rat, and these fibers are plastic in response to changes in the hormonal status of the animal (20,22,23). Finally, Hoffmann et al (16) have proposed a mechanism by which skeletal muscle afferent projections to the hypothalamus can function in the regulation of opioids.…”
mentioning
confidence: 99%